A numerical model including thermodynamic equilibrium, kinetic control and surface complexation in order to explain cation type effect on chloride binding capability of concrete. (10th December 2018) - Tran, Van Quan; Soive, Anthony; Bonnet, Stéphanie; Khelidj, Abdelhafid
Highlights: A reactive transport model with reaction kinetics and surface complexation is proposed. Chloride binding capability of CEM II exposed to chloride solutions is studied. Chloride binding capability decreases with cation type: Ca 2+ > Mg 2+ > Na + = K + . The higher the pH is, the lower the chloride is absorbed on C-S-H. Sulfates reduce chloride binding capability because of sulfate absorption on C-S-H. Abstract: The impact of cation type, sulphate and pH on chloride binding is studied using a numerical model combining thermodynamic equilibrium, kinetics and surface complexation. First, the model is validated by comparing numerical and experimental results obtained on a CEM II concrete material exposed to NaCl, KCl, MgCl 2 and CaCl 2 solutions. Then, the numerical results are discussed to improve our understanding of the differences in chloride binding capability generally observed in the literature. A strong coupling between cation, pH and sulfate affecting chloride binding is highlighted. After six months of exposure, chloride binding due to Kuzel's salt formation has little effect on chloride binding capability whatever the chloride salt solution. The results also confirm the existence of a relationship between pH and chloride binding capability previously observed experimentally in the literature. When some sulfate ions are present in the chloride solution, they reduce the chloride binding capability because of the sulfate absorption process on C-S-H.